2020
DOI: 10.1051/e3sconf/202017605016
|View full text |Cite
|
Sign up to set email alerts
|

The role of human capital in the digitalization of the country’s agriculture

Abstract: Many agricultural enterprises in our country are working in crisis conditions. Therefore, the formation of human capital in modern conditions is a continuation of the strategic goals of the enterprise, where each enterprise has its own goals, performance and development prospects. Currently, distance education is considered on the same equal basis as full- time education in higher education institutions. Intellectual and innovative activities become the main ones in training. That is why human capital is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This study used empirical modeling to determine the qualitative characteristics of the effectiveness of human capital at the current stage of development of business digitalization in Ukraine. The proposed approach, in contrast to those available in the scientific literature on the consideration of the problems of human capital compliance to the level of the digitalization of the economy (Voronin et al, 2020;Hu, 2021), was based on assessing the efficiency of human resources, not productivity (Jeske, Würfels & Lennings, 2021). This allows us to consider the priority of the human factor in the formation of the digital market space and not the scientific and technical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used empirical modeling to determine the qualitative characteristics of the effectiveness of human capital at the current stage of development of business digitalization in Ukraine. The proposed approach, in contrast to those available in the scientific literature on the consideration of the problems of human capital compliance to the level of the digitalization of the economy (Voronin et al, 2020;Hu, 2021), was based on assessing the efficiency of human resources, not productivity (Jeske, Würfels & Lennings, 2021). This allows us to consider the priority of the human factor in the formation of the digital market space and not the scientific and technical factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, digitalization of economic activity is understood by most scientists as a new structural change in the technological structure of the economy, in which digital data, processing large volumes of it and the use of analysis results are the key factors of production (Ragnedda, 2018). Many scientific studies in the field of human capital were based on using a variety of empirical and analytical tools and confirmed the close relationship between digitalization, innovation, and the productivity of human capital (Voronin et al, 2020;Hu, 2021;Jeske, Würfels & Lennings, 2021) The effective development of human capital and the possibility of productive use to ensure sustainable development of economic ties and the establishment of stable ties with business, science, and education in the context of informatization of economic activity is increasingly acquiring the status of a priority strategic direction for the development of the modern economy (Jeske, Würfels & Lennings, 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Saiz-Rubio and Rovira-Más (2019), and several other authors, draw attention to the increasing age of American and European farmers, and their reluctance to accept new technologies and modern tools. According to Voronin et al (2020), the younger generation is important in relation to technology, because the ability to work and innovate very often gradually disappears with age. According to Bowen and Morris (2019), the development of digital and marketing skills are key drivers for further entrepreneurial activity among agrifood businesses.…”
Section: The Theoretical Basis Of the Agriculture Digitisation Processmentioning
confidence: 99%
“…Analysis of the content of articles showed that only individual authors (M. Anghela, 2014, V. Abraukhova, 2020, B.A. Voronin, 2020) focus the attention of the pedagogical community on upbringing problems, justifying innovative ways to solve them [3,4,5]. A number of scientists (V. Cherenkov, N. Cherenkova, 2018; N. Iivari, S. Sharma, L. Ventä-Olkkonen, 2020) also suggest restoring the upbringing function in higher education, for example, through the geopolitical socialization of students [6].…”
Section: Introductionmentioning
confidence: 99%